Bay-Dissymmetrical hetero- and Aza-Benzannulated PeryleneDiimides as new n-type semiconductors. Issue 40 (7th September 2022) - Goujon, Antoine; Rocard, Lou; Melville, Hayley; Cauchy, Thomas; Cabanetos, Clément; Dabos-Seignon, Sylvie; Hudhomme, Piétrick
Abstract : AzaBenzannulated PeryleneDiimides (AzaBPDIs) and their nitrogen, sulphur and selenium bay -functionalized derivatives are introduced herein as a new class of n-type semiconductors. Abstract : AzaBenzannulated PeryleneDiimides (AzaBPDIs) and their nitrogen, sulphur and selenium bay -functionalized derivatives are introduced herein as a new class of n-type semiconductors. Heteroatoms were inserted in one bay prior to the application of a visible-light-driven cyclisation strategy closing a six-membered ring comprising a nitrogen atom on the opposite bay . The electronic and optical properties of these compounds were studied both in solution and in thin films. With the exception of the nitrogen-appended derivative, all dyes behaved as n-type semiconductors, with little to no sensitivity to thermal annealing. This demonstration opens the door to the design of more complex AzaBPDI based architectures.